Multiliteracy Pedagogy for Maritime Vocational English: A Quasi-Experimental Study in Shipping Management - Marudut Bernadtua Simanjuntak; Meilinasari Nurhasanah Hutagaol; Suhartini Suhartini (GLENS: Global English Insights Journal, 2026)
Despite the increasing complexity of contemporary maritime operations, conventional English for Specific Purposes (ESP) approaches in maritime vocational education inadequately prepare shipping management students for the complex multimodal, digital, and sociocultural communicative demands these operations require. This study investigates the design, implementation, and efficacy of a Multiliteracy Pedagogy-Based Maritime English Communication Learning Model (MPKBIM) for vocational shipping management students in Indonesian maritime institutes. Drawing on systemic functional linguistics (SFL), genre-based pedagogy, multiliteracy theory, and critical ESP, a quasi-experimental design, informed by a mixed-methods needs analysis that shaped the curriculum prior to implementation, was employed with 120 vocational students across traditional and multiliteracy-enhanced curricula over one academic year. Data were collected through pre- and post-intervention assessments, communicative genre portfolios, classroom observations, and semi-structured interviews with 36 maritime professionals, 18 instructors, and 48 students. Results demonstrate that MPKBIM students significantly outperformed comparison students in multimodal communication (78% vs. 31%), digital communication competence (72% vs. 38%), and critical communicative understanding. The study provides empirical evidence that multiliteracy pedagogy effectively bridges the gap between conventional maritime English training and the actual communicative demands of contemporary maritime management, offering a theoretically grounded and empirically validated curriculum model for maritime vocational education reform.